2019
DOI: 10.1002/pssb.201800527
|View full text |Cite
|
Sign up to set email alerts
|

Trap‐Related Breakdown and Filamentary Conduction in Carbon Doped GaN

Abstract: A breakdown phenomenon is studied in thin carbon doped GaN layers (GaN:C; carbon concentration 10 19 cm À3 ) embedded between a top metal electrode and bottom n-doped GaN (n-GaN). When slowly sweeping positive bias V at the top electrode up and down, a hysteresis is found with transitions to on-and off-states at voltages V bd;up and V bd;down ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Finally, we note that strong non-linearity can occur in the carbon doped GaN system under some circumstances. Negative differential resistance in the IV characteristics of GaN:C to Si doped GaN diodes [19], and relaxation oscillation behavior in substrate ramp experiments [20], suggest that the transport cannot always be described by band edge transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that strong non-linearity can occur in the carbon doped GaN system under some circumstances. Negative differential resistance in the IV characteristics of GaN:C to Si doped GaN diodes [19], and relaxation oscillation behavior in substrate ramp experiments [20], suggest that the transport cannot always be described by band edge transport.…”
Section: Discussionmentioning
confidence: 99%
“…The key novelty is the recognition that the leakage paths through the UID GaN are non-Ohmic and we propose that this can be explained by the presence of a previously unrecognised diode barrier between the dislocation core and the 2DEG. 19 cm −3 (measured by secondary ion mass spectrometry), 300 nm UID GaN channel, and AlGaN barrier (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…2 suggest the presence of a snapback or negative-resistance mechanism associated with the localized transport through the more heavily carbon doped layer. We note that Koller et al [14] have reported negative resistance and a localized breakdown mechanism in carbon doped bulk GaN structures, with associated localized EL light emission. Some of their localized breakdowns were pinned to dislocations, although here the precise nature of the defects is unknown.…”
Section: Discussionmentioning
confidence: 50%
“…Note the hysteresis of Run3 and Run4 tends to decrease when increasing the ramping time (not shown here). This time-related turn-on behavior might relate to bistability between the ON-state filamentary conduction [21] and SCLC. The complicated forward I -V behavior can be interpreted with the help of the DLTS measurements and I -V characteristics at different temperatures, which will be discussed in Sections III-C and III-D. Fig.…”
Section: B I-v Characteristicsmentioning
confidence: 99%
“…The electrons in the GaN:Si layer and the holes in the GaN:C layer then can easily overcome the barrier, and the device turns on steeply. In addition, despite the holes capture mechanism, we would like to notice that other trap-and fieldrelated mechanisms can be considered leading to the device turning on [21].…”
Section: Carrier Transport Mechanismmentioning
confidence: 99%